The Impact of Blended Learning Type Flipped Classroom on Autonomous Mathematics Learning - Ahmad Ahmad (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2021)
The purpose of this study is to determine (1) the autonomous of learning mathematics taught by the blended learning model of the flipped classroom type in as the senior class in a junior high school in Sokaraja in academi year of 2019/2020, (2) the autonomous of learning mathematics taught by conventional learning models in as the senior class in a junior high school in Sokaraja in academi year of 2019/2020, and (3) whether the learning independence is maintained. A quasi-experimental approach with a non-equivalent control group was employed in this research. The samples utilized in this research were divided into two classes, with one class serving as the experimental class and the other serving as the control class. As a data collecting technique, the independence test was used. The information was then examined using descriptive statistics and the t-test. Based on the findings the following conclusions may be drawn: There are variations in students' learning independence while studying mathematics. Students who get mixed learning model type flipped classroom and students who receive traditional learning models have curved sides.